Pemberdayaan UMKM tentang Pentingnya Adaptasi Digital dan Legalitas Usaha di Limpomajang Kec. Majauleng Kab. Wajo - Yuniarti, A. (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
MSMEs (Micro, Small, and Medium Enterprises) play a crucial role in advancing the national economy and have the potential to improve the quality of life of the community. However, this sector often faces challenges, especially in terms of digital adaptation and licensing, which have yet to receive adequate solutions. In response to this, community service activities are conducted with the aim of educating and raising awareness of the importance of empowering MSMEs, especially in the Limpomajang Village. The research described in this article is conducted using a descriptive qualitative approach, collecting data through observation, interviews with MSME actors, and literature studies from various sources. One of the outcomes of this community service is the socialization to MSMEs operating in various industrial sectors. This socialization emphasizes the need to empower MSMEs, focusing on enhancing human resource capabilities, such as sales digitalization training and licensing processes. As a result, MSMEs are better informed about online promotion strategies, non-cash payment methods, and the importance of having the proper licenses. It is hoped that this activity will provide long-term benefits for the development of MSMEs in Limpomajang Village, Majauleng Subdistrict, Wajo District